2010
DOI: 10.1111/j.1464-410x.2009.08808.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐catenin expression and claudin expression pattern as prognostic factors of prostatic cancer progression

Abstract: OBJECTIVE To investigate the patterns of expression of the junctional proteins β‐catenin and claudins in different prognostic groups of patients with prostatic cancer, to determine their value as prognostic markers. PATIENTS AND METHODS We evaluated the samples of 30 patients who had a radical prostatectomy for organ‐confined cancer (pT2N0M0), men with clinically advanced cancer, and a control group with benign prostatic hyperplasia. Using immunohistochemistry applied to tissue microarrays, each group was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It has been observed that β-Catenin expression and localization change during human prostate cancer progression, however, results are inconsistent. Several studies have seen an increase in β-Catenin expression and nuclear localization in late stage cancer samples, while others have reported a loss in nuclear expression in advanced tumours [12], [13], [14], [15], [16]. In addition to its role in WNT signalling, β-Catenin can act as a co-factor with AR, suggesting it has a role in castration-resistant disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that β-Catenin expression and localization change during human prostate cancer progression, however, results are inconsistent. Several studies have seen an increase in β-Catenin expression and nuclear localization in late stage cancer samples, while others have reported a loss in nuclear expression in advanced tumours [12], [13], [14], [15], [16]. In addition to its role in WNT signalling, β-Catenin can act as a co-factor with AR, suggesting it has a role in castration-resistant disease.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide evidence for functional overlap between GLI1 and lipocalin 2 in breast cancer and, accordingly, the expression of both proteins is associated with the ER − phenotype [49], [50], [51], [52]. Similarly, although the tight junction protein claudin 1 (CLDN1) is often decreased in breast tumours [53], [54], [55], high expression has been described in ER − tumours [56], [57]. In the prostate, claudin1 expression is high in the basal layer of benign tissue and its expression decreases with increasing tumour aggressiveness [58], [59].…”
Section: Discussionmentioning
confidence: 95%
“…Our results suggested that patients with organ-confined (OCC) and advanced cancer (CAC) were subsets with distinct claudin expression profiles, specifically, claudin-4 and -5 was expressed at higher levels in PCa with poor prognosis [17]. Elevated membranous claudin-4 expression was described by others as well to be a marker of poor prognosis in prostate cancer [18].…”
Section: Introductionmentioning
confidence: 84%